CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN AUDIT REPORT LAG - Debbi Chyntia Ovami; Reza Hanafi Lubis (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
This research purpose is to examine and analyze the effects of corporate governance (measured through managerial ownership, institutional ownership, and independent commissioners) and size to audit report lag on real estate and property companies in Indonesia. This type of research is causal research. Population in this research is Real Estate and Property firms listed on Indonesia Stock Exchange in period 2012-2016 number 61 company. The sampling technique used is purposive sampling obtained the number of observations of 170 units of analysis. The results showed that managerial ownership, institutional ownership,independent commissioners and size had a negative and significant impact on audit report lag. Simultaneously, corporate governance had been measured by managerial ownership, institutional ownership, independent commissioners, and size has significant impact on audit report lag on real estate and property companies in Indonesia.